Low-sugar soybean protein compound solid beverage and preparation method thereof

CN122936375APending Publication Date: 2026-10-20HEILONGJIANG LAND RECLAMATION DRAGON KING FOOD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611266689.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0050]本发明通过大豆分离蛋白初级粉末的pH调节、喷雾干燥和流化床喷雾团聚,构建三维多孔团聚颗粒,使颗粒内部保留可供水分快速进入的结构路径,同时减少细粉直接冲调时易漂浮和结团的问题,有利于提升低糖固体饮品的冲调分散性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of plant protein solid beverages, and provides a low-sugar soybean protein compound solid beverage and its preparation method. The beverage comprises structured soybean protein-pectin composite particles and powdered soybean lecithin. The composite particles include a three-dimensional porous aggregated particle core formed from soybean protein isolate and a pectin interface layer disposed on the surface of the core. The particle size D50 of the core is 120-250 μm, and the pectin interface layer accounts for 1.5-6.0 wt% of the dry weight of the composite particles. Based on 100 parts by weight of the composite particles, the powdered soybean lecithin comprises 0.2-1.5 parts by weight. The sugar content of the beverage, calculated as the total amount of free monosaccharides and disaccharides, is 0-5.0 wt%, and the moisture content is 2.0-5.0 wt%. This beverage is beneficial for improving the integrity of the particle structure, dispersibility, and stability under low-sugar conditions, and is suitable for low-sugar plant protein instant foods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of plant protein solid beverage processing, specifically to a low-sugar soybean protein compound solid beverage and its preparation method. Background Technology

[0002] With the development of plant-based protein foods and low-sugar nutritional supplements, soy protein solid beverages have high application value in meal replacements, sports nutrition, elderly nutrition, and daily protein supplementation. These products typically need to be prepared quickly and maintain uniform dispersion, smooth taste, stable powder storage, and particle integrity during packaging and transportation under conditions of high protein loading and low sugar addition. For reconstituted solid beverages, protein particles must not only have sufficient porous structure to facilitate rapid water penetration but also appropriate particle strength and interfacial stability to reduce powder agglomeration, floating, settling, and particle residue after preparation. In low-sugar systems, the availability of sugar additives to improve taste and dispersion is limited, further increasing the importance of protein hydration, particle pore structure, and interfacial regulation. Therefore, developing compound solid beverages that balance structural integrity, reconstitution and dispersibility, processing window, and stability in low-sugar systems is of practical significance for improving the user experience and industrialization stability of plant-based protein foods.

[0003] Existing soy protein solid beverages often improve their reconstitution state through protein modification, spray drying, granulation, or the addition of wetting components. However, these different methods often have mutual constraints. Increasing particle density is beneficial for maintaining structure during transportation and storage, but may delay the entry of water into the particle interior; increasing porosity and agglomeration is beneficial for rapid dispersion, but may reduce the particle's resistance to breakage; enhancing polysaccharide interface regulation is beneficial for the suspension and stability of low-sugar systems, but may narrow the window for spraying, drying, and mixing processes. Chinese patent document CN110250316B discloses a process for producing fast-dissolving soy protein isolate, which improves the dispersibility of high-concentration reconstitution through enzyme treatment, drying, and granulation. However, its focus is mainly on protein raw material modification and granulation, lacking specific arrangements for the structural matching relationship between the porous protein core, pectin interface layer, and powdered soy lecithin compound. Existing studies have evaluated the rheology, particle size, and stability of soy protein isolate and high-ester citrus pectin composite systems. However, most of these studies have focused on emulsion models and have limited specific disclosures on the powder structure and packaging adaptability of low-sugar solid instant beverages. Summary of the Invention

[0004] This invention uses three-dimensional porous soy protein isolate aggregates to provide rapid wetting and dispersion, a pectin interface layer to restrict particle loosening and regulate interface state, and powdered soy lecithin to improve the wetting path of low-sugar powders for reconstitution. By matching the structural hierarchy and compound ratio, the adverse effects of densification and loosening are weakened, thus achieving a balance between stable processing and good reconstitution applications.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] A low-sugar soy protein compound solid beverage, in solid form before reconstitution, comprises structured soy protein-pectin composite particles and powdered soy lecithin.

[0007] The structured soybean protein-pectin composite particles include a core formed of soybean protein isolate and a pectin interface layer formed of pectin disposed on the surface of the core. The core is a three-dimensional porous aggregated particle with a particle size D50 of 120-250 μm. The pectin interface layer accounts for 1.5-6.0 wt% of the dry weight of the structured soybean protein-pectin composite particles. Based on 100 parts by weight of the structured soybean protein-pectin composite particles, the amount of powdered soybean lecithin is 0.2-1.5 parts by weight. Based on the total weight of the low-sugar soybean protein compound solid beverage in solid form before reconstitution, the sugar content of the low-sugar soybean protein compound solid beverage, calculated as the total amount of free monosaccharides and disaccharides, is 0-5.0 wt%, and the moisture content is 2.0-5.0 wt%.

[0008] Furthermore, the particle size D50 of the three-dimensional porous agglomerates is 145-230 μm.

[0009] Furthermore, the pectin interface layer accounts for 2.0-5.2 wt% of the dry weight of the structured soybean protein-pectin composite particles.

[0010] Furthermore, the primary powder of soy protein isolate is prepared through the following steps and used as a raw material for preparing the three-dimensional porous aggregated particles:

[0011] A1. Mix soy protein isolate with deionized water;

[0012] A2. Adjust the pH of the system to 10.2-11.2 with sodium hydroxide and stir at 20-35℃ for 15-35 min;

[0013] A3. Adjust the pH of the system to 6.4-7.0 using anhydrous citric acid under stirring conditions;

[0014] A4. Spray dry the system after pH adjustment, with an inlet air temperature of 160-185℃ and an outlet air temperature of 75-90℃, to obtain the primary soy protein isolate powder, wherein the particle size D50 of the primary soy protein isolate powder is 20-80μm.

[0015] Furthermore, the three-dimensional porous agglomerated particles are prepared through the following steps:

[0016] B1. Add the primary soy protein isolate powder to a fluidized bed;

[0017] B2. Based on 100 parts by weight of the soy protein isolate primary powder, 8-20 parts by weight of deionized water are used as the agglomeration liquid for spray agglomeration. The spray agglomeration is carried out under the conditions of bed temperature of 45-60℃, spray pressure of 0.05-0.20MPa, and spray agglomeration time of 12-25min.

[0018] B3. Continue drying the spray-agglomerated material for 10-20 minutes to obtain the three-dimensional porous agglomerated particles.

[0019] Furthermore, the pectin interface layer is constructed through the following steps:

[0020] C1. Mix pectin with deionized water;

[0021] C2. Stir the mixture of pectin and deionized water at 50-70℃ for 15-40 min to obtain a pectin solution with a mass fraction of 1.0-4.0 wt%.

[0022] C3. Spray the pectin solution onto the surface of the three-dimensional porous aggregated particles. The bed temperature during spraying is 40-55℃, and the spraying time is 10-25 minutes.

[0023] C4. Dry the sprayed particles until the moisture content is 2.0-5.0 wt% based on the mass of the structured soybean protein-pectin composite particles, to obtain the structured soybean protein-pectin composite particles.

[0024] Furthermore, the low-sugar soy protein compound solid beverage is prepared through the following steps:

[0025] D1. Take the structured soybean protein-pectin composite particles and the powdered soybean lecithin, and add food-grade glucose when the target sugar content of the low-sugar soybean protein compound solid beverage is greater than 0 wt% and not higher than 5.0 wt%. Add all raw materials to the mixing equipment.

[0026] D2. Mix at 20-35℃ and 15-30r / min for 5-20min;

[0027] D3. After nitrogen replacement, the mixed materials are sealed and packaged to obtain the low-sugar soybean protein compound solid beverage.

[0028] Furthermore, the low-sugar soy protein compound solid beverage has the following technical features:

[0029] The loose density of the structured soybean protein-pectin composite granules is 200-400 kg / m³.

[0030] The degree of esterification of the pectin is 50-80%.

[0031] As a concept of this invention, the present invention employs a design combining structured soybean protein-pectin composite particles and powdered soybean lecithin, primarily aimed at achieving a synergistic balance between particle structural integrity and dispersibility during reconstitution. Existing soybean protein solid beverages, if maintaining integrity during storage and packaging by increasing particle density, suffer from a longer path for water to enter the particle interior, leading to clumping and slow dispersion during reconstitution. Conversely, if hydration speed is improved through porous agglomeration, the particles are prone to loosening and breakage during processing and mixing, affecting powder uniformity. This invention forms three-dimensional porous agglomerated particles of soybean protein isolate, preserving hydration channels. A pectin interface layer regulates particle surface constraint, and powdered soybean lecithin improves the wetting state of the low-sugar system, thus achieving a balance between particle strength, dispersion speed, and reconstitution stability within the same product system.

[0032] This invention also discloses a method for preparing a low-sugar soy protein compound solid beverage, comprising the following steps:

[0033] S1. Provides pre-prepared structured soybean protein-pectin composite particles, wherein the structured soybean protein-pectin composite particles are obtained through the following steps: Soybean protein isolate is mixed with deionized water, the pH of the system is adjusted to 10.2-11.2 with sodium hydroxide, and stirred at 20-35℃ for 15-35 min; under stirring conditions, the pH of the system is adjusted back to 6.4-7.0 with anhydrous citric acid; the pH-adjusted system is spray-dried at an inlet air temperature of 160-185℃ and an outlet air temperature of 75-90℃ to obtain primary soybean protein isolate powder; the primary soybean protein isolate powder is added to a fluidized bed, with 100 parts by weight of the primary soybean protein isolate powder... Using 8-20 parts by mass of deionized water as the agglomeration solution, spray agglomeration is carried out for 12-25 minutes at a bed temperature of 45-60℃ and a spray pressure of 0.05-0.20MPa, followed by drying for 10-20 minutes to obtain three-dimensional porous agglomerated particles. Pectin is mixed with deionized water and stirred at 50-70℃ for 15-40 minutes to obtain a pectin solution with a mass fraction of 1.0-4.0wt%. The pectin solution is sprayed onto the surface of the three-dimensional porous agglomerated particles at a bed temperature of 40-55℃ for 10-25 minutes, and the sprayed particles are dried to a moisture content of 2.0-5.0wt% to obtain the structured soybean protein-pectin composite particles.

[0034] S2. When the target sugar content of the low-sugar soybean protein compound solid beverage is 0 wt%, raw materials for which free monosaccharides and disaccharides are not detected by the sugar content detection method are selected, and food-grade glucose is not added. The structured soybean protein-pectin composite particles are mixed with the powdered soybean lecithin to obtain a mixture. When the target sugar content of the low-sugar soybean protein compound solid beverage is greater than 0 wt% and not higher than 5.0 wt%, food-grade glucose calculated based on the total mass of the final product, the content of free monosaccharides and disaccharides in each raw material, and the target sugar content is mixed with the structured soybean protein-pectin composite particles and the powdered soybean lecithin to obtain a mixture.

[0035] S3. Package the mixture to obtain the low-sugar soy protein compound solid beverage.

[0036] Further, in step S2, the powdered soybean lecithin is sieved through a sieve with a pore size of 150-250μm before being added, and the sieve-undersized material is collected; in step S3, the mixture is sealed and packaged after being purged with nitrogen.

[0037] Furthermore, the structured soybean protein-pectin composite particles refer to composite particles that use primary soybean protein isolate powder as upstream particle raw material, which are agglomerated in a fluidized bed spray to form three-dimensional porous aggregated particles with a particle size D50 of 120-250μm as the core, and are then coated with pectin solution and dried to form a pectin interface layer on the surface of the core. The composite particles are used as protein particle components in low-sugar soybean protein compound solid beverages, mixed with powdered soybean lecithin.

[0038] Furthermore, in the preparation of primary soy protein isolate powder, soy protein isolate is mixed with deionized water to form a protein dispersion system. The pH value of the protein dispersion system is adjusted to 10.2-11.2 and stirred at 20-35℃ for 15-35 min. Then, under stirring conditions, the pH value of the system is adjusted back to 6.4-7.0. The system after pH adjustment is used as a spray-feed suspension. The raw material solids content of the spray-feed suspension is 10-18 wt%, which is calculated based on the feed mass of soy protein isolate and deionized water, i.e.: Raw material solids content = feed mass of soy protein isolate / (feed mass of soy protein isolate + feed mass of deionized water) × 100%, excluding the mass introduced by the pH adjuster. The spray-feed suspension is spray-dried at an inlet air temperature of 160-185℃ and an outlet air temperature of 75-90℃ to form primary soy protein isolate powder with a particle size D50 of 20-80 μm.

[0039] Furthermore, in the detection of particle size D50, spray-dried primary soy protein isolate powder, fluidized bed agglomerated three-dimensional porous aggregated particles, and dried structured soy protein-pectin composite particles can all be used as test samples. The test samples are dispersed in a dry powder state, and the particle size distribution is tested. The D50 is recorded based on the particle size at which the cumulative volume distribution reaches 50%. Specifically, the D50 of primary soy protein isolate powder is used to determine its particle size as 20-80 μm, the D50 of three-dimensional porous aggregated particles is used to determine its particle size as 120-250 μm, and the D50 of structured soy protein-pectin composite particles is used to characterize its dry powder particle size distribution.

[0040] Furthermore, in the preparation process of the three-dimensional porous aggregated particles, 100 parts by weight of primary soybean protein isolate powder is used as fluidized bed feed, and 8-20 parts by weight of deionized water is used as agglomeration liquid. The agglomeration liquid is sprayed onto the primary soybean protein isolate powder at a bed temperature of 45-60℃ and a spray pressure of 0.05-0.20MPa for a spray agglomeration time of 12-25 min. The material after spray agglomeration continues to dry for 10-20 min. The resulting three-dimensional porous aggregated particles are used as core particles in the pectin interface layer construction step.

[0041] Furthermore, during the construction of the pectin interface layer, pectin is mixed with deionized water and stirred at 50-70℃ for 15-40 min to obtain a pectin solution with a mass fraction of 1.0-4.0 wt%. The pectin solution is then sprayed onto the surface of three-dimensional porous aggregated particles at a bed temperature of 40-55℃ for 10-25 min. The sprayed particles are then dried to a moisture content of 2.0-5.0 wt% to obtain structured soybean protein-pectin composite particles.

[0042] Furthermore, the pectin interface layer mass fraction was calculated based on the dry mass of the three-dimensional porous aggregated particles before spraying and the dry mass of the structured soybean protein-pectin composite particles after spraying and drying. The calculation formula is: Pectin interface layer mass fraction = [(Dry mass of structured soybean protein-pectin composite particles after spraying and drying - Dry mass of three-dimensional porous aggregated particles before spraying) / Dry mass of structured soybean protein-pectin composite particles after spraying and drying] × 100%; where the dry masses before and after spraying are the dry basis masses of the same batch of material after deducting moisture. The obtained pectin interface layer mass fraction was used to determine that the pectin interface layer accounted for 1.5-6.0 wt% of the dry mass of the structured soybean protein-pectin composite particles.

[0043] Furthermore, the degree of esterification of pectin is measured as the molar percentage of esterified carboxyl groups in the pectin raw material relative to the total carboxyl groups. The degree of esterification of the pectin raw material is determined before mixing with deionized water. Pectin with a degree of esterification of 50-80% is introduced into the pectin solution preparation step. The resulting pectin solution is used to construct a pectin interface layer on the surface of three-dimensional porous aggregated particles.

[0044] Furthermore, the loose packing density of the structured soybean protein-pectin composite granules was determined using the dried structured soybean protein-pectin composite granules as the test sample. The test sample was placed into a container of known volume without being compacted, and the mass of the test sample entering the container of known volume was recorded. The loose packing density was calculated by dividing the mass of the test sample by the volume of the container of known volume. The resulting loose packing density was used to determine that the loose packing density of the structured soybean protein-pectin composite granules was 200-400 kg / m³.

[0045] Furthermore, the sugar content was based on the total mass of the low-sugar soy protein compound solid beverage in solid form before reconstitution, and calculated using the total amount of free monosaccharides and disaccharides in the solid sample before reconstitution. The solid sample of the low-sugar soy protein compound solid beverage was mixed with water for extraction, and insoluble matter was separated. The content of monosaccharides and disaccharides in the extract was detected, and the sugar content was obtained by summing the contents of each monosaccharide and disaccharide. The resulting sugar content was used to determine that the sugar content of the low-sugar soy protein compound solid beverage was 0-5.0 wt%. A sugar content of 0 wt% indicates that no free monosaccharides or disaccharides were detected using the above detection method.

[0046] Furthermore, the moisture content was determined by measuring the dry weight loss of the solid sample before reconstitution. The moisture content was calculated as the percentage of the difference in mass before and after drying relative to the mass of the sample before drying. The resulting moisture content was used to determine that the moisture content of the low-sugar soy protein compound solid beverage was 2.0-5.0 wt%.

[0047] Furthermore, in the preparation process of the low-sugar soy protein compound solid beverage, the powdered soy lecithin is sieved through a sieve with a pore size of 150-250μm before being added, and the sieved material is collected. The sieved powdered soy lecithin is then mixed with the structured soy protein-pectin composite particles at 20-35℃ and 15-30r / min for 5-20min. When the target sugar content of the low-sugar soy protein compound solid beverage is greater than 0wt% and not higher than 5.0wt%, the amount of food-grade glucose added is calculated based on the total mass of the final product, the content of free monosaccharides and disaccharides in the raw materials, and the target sugar content. The food-grade glucose is then mixed together with the sieved powdered soy lecithin and the structured soy protein-pectin composite particles. When the target sugar content is 0wt%, no food-grade glucose is added. The mixed material is then sealed and packaged after nitrogen replacement to obtain the low-sugar soy protein compound solid beverage in solid form before reconstitution.

[0048] Three-dimensional porous agglomerated particles primarily address the issues of rapid water penetration and protein particle dispersion during the preparation of low-sugar soy protein compound solid beverages. However, relying solely on the porous agglomerated structure may lead to loosening or fragmentation of particles during spraying, mixing, packaging, and transportation due to the high porosity, thus affecting powder uniformity. The pectin interface layer mainly regulates the particle surface state and structure retention capacity; however, excessively high pectin interface layer concentration may overly restrict the particle surface, reducing hydration rate and compressing the processing window. This invention achieves a balance between the primary powder particle size of soy protein isolate, fluidized bed agglomeration conditions, pectin solution concentration, spraying time, and the amount of powdered soy lecithin. This balance allows the porous core to provide a wetting path, the pectin interface layer to correct the tendency for structural loosening, and the powdered soy lecithin to improve powder wetting and spreading, ultimately addressing the limitations of each other.

[0049] Beneficial technical effects

[0050] This invention constructs three-dimensional porous aggregated particles by adjusting the pH of primary soy protein isolate powder, spray drying, and fluidized bed spray agglomeration. This allows the particles to retain structural pathways for rapid water entry, while reducing the problems of floating and clumping when fine powder is directly mixed. This is beneficial for improving the dispersibility of low-sugar solid beverages.

[0051] This invention constructs a pectin interface layer on the surface of three-dimensional porous aggregated particles, enabling the pectin to form a moderate interface regulation on the surface of protein particles, reducing the tendency of porous particles to become loose during subsequent mixing, packaging and storage, and helping to maintain the dispersion state of the particles after reconstitution in low-sugar systems, thereby improving the balance between structural integrity and stability in use.

[0052] This invention combines structured soybean protein-pectin composite particles with powdered soybean lecithin and limits the amount of powdered soybean lecithin used. This allows the lecithin to improve the wetting and spreading of particles during the powder preparation process, reducing insufficient wetting caused by the lack of sugar additives under low sugar conditions, while avoiding the adverse effects of excessive oily components on powder flow and preparation taste.

[0053] This invention, through the synergistic limitation of parameters such as pectin esterification degree, pectin interface layer mass fraction, bulk density, particle size D50, moisture and sugar content, ensures consistent process controllability across multiple levels, including particle structure, interface state, powder storage and reconstitution. Compared to pure protein powder or single granulated powder, it is more suitable for low-sugar plant protein reconstitution applications. Attached Figure Description

[0054] Figure 1 This is a single-factor effect diagram of changing the pectin interface layer mass fraction based on the intermediate parameter scheme shown in Example 3.

[0055] Figure 2 This is a single-factor effect diagram of changing the amount of powdered soybean lecithin based on the intermediate parameter scheme shown in Example 3.

[0056] Figure 3 The single-factor effect diagram is shown for changing the D50 of three-dimensional porous aggregated particles based on the intermediate parameter scheme shown in Example 3.

[0057] Figure 4 This is a single-factor effect diagram showing the effect of changing the amount of deionized water used for spray agglomeration based on the intermediate parameter scheme shown in Example 3.

[0058] Figure 5 The dry powder particle size difference distribution diagrams are for Example 1, Comparative Example 4, and Comparative Example 10.

[0059] Figure 6 The cumulative particle size distribution of dry powder in Example 1, Comparative Example 4, and Comparative Example 10 is shown in the diagram.

[0060] Figure 7 The images are statistical graphs of particle morphology for Example 1, Comparative Example 4, and Comparative Example 10.

[0061] Figure 8 The image shows the scatter plot of the pectin interface layer mass fraction for Examples 1, 6, and 9.

[0062] Figure 9 The diagram shows the mixing, wetting, and dispersion process of Example 1, Comparative Example 7, and Comparative Example 11.

[0063] Figure 10 The diagram shows the precipitation stabilization process of the reconstituted solutions in Examples 1, 9, and 11.

[0064] Figure 11 The graph shows the relationship between the loose packing density and the fine powder content after shaking for Examples 1, 4, and 8.

[0065] Figure 12 The image shows the scatter plot of the fine powder ratio after oscillation for Examples 1, 4, and 8.

[0066] Figure 13 The images show a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 10; where a is a macroscopic optical photograph of the final product of Example 1 and b is a macroscopic optical photograph of the final product of Comparative Example 10.

[0067] Figure 14 The images show a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 10; where a is a low-magnification SEM image of the final product of Example 1; b is a low-magnification SEM image of the final product of Comparative Example 10; c is a medium-magnification SEM image of the final product of Example 1; d is a medium-magnification SEM image of the final product of Comparative Example 10; e is a high-magnification SEM image of the final product of Example 1; and f is a high-magnification SEM image of the final product of Comparative Example 10. Detailed Implementation

[0068] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.

[0069] Unless otherwise stated, the moisture content at each stage refers to the measured mass fraction of the sample at the corresponding stage; the moisture and sugar content of the finished product are based on the measured values ​​of the solid sample after mixing, nitrogen replacement, and sealing.

[0070] Example 1

[0071] S1: Primary powder preparation, using commercially available food-grade soy protein isolate as the protein raw material, with a dry basis protein content of not less than 90%, and no detectable free monosaccharides or disaccharides. 1000g of soy protein isolate was weighed and mixed with 9000g of deionized water, and mechanically stirred at 300r / min for 10min under normal pressure and air atmosphere to form a protein dispersion system with a raw material solid content of 10wt%. The pH of the system was adjusted to 10.2 with a 1.0mol / L sodium hydroxide aqueous solution, and stirred at 300r / min for 15min at 20℃. Subsequently, food-grade anhydrous citric acid was added in batches under stirring at 300r / min to adjust the pH of the system back to 6.4, and stirring was continued for 5min to stabilize the pH. The pH-adjusted system was then fed into a spray dryer with an inlet air temperature of 160℃, an outlet air temperature of 75℃, and an atomization pressure of 0.12MPa. After feeding, the dried powder was collected to obtain primary soy protein isolate powder. The particle size D50 of the primary soy protein isolate powder in this embodiment was measured to be 20 μm in dry powder dispersion.

[0072] S2: Preparation of three-dimensional porous agglomerated particles. 1000g of primary soybean protein isolate powder from this embodiment was added to a fluidized bed, and the fluidizing air was turned on. The bed temperature was stabilized at 45℃. 80g of deionized water was used as the agglomeration liquid and sprayed into the fluidized bed through a nozzle at a spray pressure of 0.05MPa for 12 minutes. After spraying, the bed temperature was maintained at 45℃ for another 10 minutes of drying. The discharged material was then lightly sieved through an 80-mesh sieve to obtain three-dimensional porous agglomerated particles. The three-dimensional porous agglomerated particles of this embodiment were light milky white powders with no obvious hard lumps. The particle size D50 measured in the dry powder state was 120μm.

[0073] S3: Construction of the pectin interface layer. Commercially available food-grade pectin with an esterification degree of 50% and a purity of not less than 90% was selected. 15.3g of pectin was weighed and added to 1514.7g of deionized water, and stirred at 250r / min for 15min at 50℃ to obtain a pectin solution with a mass fraction of 1.0wt%. 1000g of the three-dimensional porous aggregated particles of this embodiment (dry basis) was added to a fluidized bed, and the bed temperature was stabilized at 40℃. The pectin solution was sprayed onto the particle surface for 10min. After spraying, hot air at 45℃ was continued to dry until the particle moisture content was 2.0wt%, resulting in structured soybean protein-pectin composite particles. The pectin interface layer of this embodiment has a mass fraction of 1.5wt% and a bulk density of 200kg / m³.

[0074] S4: Compounding and Packaging. Take 1000g of the structured soybean protein-pectin composite granules of this embodiment, and 2.0g of commercially available food-grade powdered soybean lecithin with a purity of not less than 95%. Before adding, sieve the powdered soybean lecithin through a 150μm sieve and collect the sieved material. Add the structured soybean protein-pectin composite granules and the sieved powdered soybean lecithin to a low-speed mixer and mix for 5 minutes at 20℃ and 15r / min. After mixing, purge with nitrogen gas of not less than 99.9% purity and then seal and package to obtain a low-sugar soybean protein compound solid beverage in solid form before reconstitution. No free monosaccharides or disaccharides were added in this embodiment, and the finished solid sample was recorded as not detected according to the sugar content detection method described in this specification.

[0075] Quality testing methods and results: Three parallel tests were performed on the solid samples of this embodiment. Particle size D50 was determined by testing the particle size distribution after dry powder dispersion and recording the particle size at which the cumulative volume distribution reached 50%. The average D50 of the three-dimensional porous aggregated particles was 120 μm, with a standard deviation of 4 μm. The pectin interface layer mass fraction was calculated based on the difference in dry mass before and after spraying, with an average of 1.5 wt% and a standard deviation of 0.1 wt%. Moisture content was determined by the loss on drying method, with an average of 2.0 wt% and a standard deviation of 0.1 wt%. Sugar content was calculated by summing the extracted free monosaccharides and disaccharides, and was recorded as undetectable. Loose packing density was calculated by dividing the uncompacted packing mass by the container volume, with an average of 200 kg / m³ and a standard deviation of 6 kg / m³.

[0076] Features and application scenarios of this embodiment

[0077] This embodiment adopts a relatively conservative low-ratio scheme, with lower amounts of pectin interface layer and powdered soybean lecithin, and the process conditions are more moderate. The resulting powder has lower moisture content and lower bulk density, making it suitable for instant plant protein drinks that emphasize low sugar, low additive content and a lighter powder state.

[0078] Example 2

[0079] In this embodiment, a low-sugar soy protein compound solid beverage is prepared using commercially available food-grade soy protein isolate, deionized water, food-grade pectin, food-grade powdered soy lecithin, and food-grade glucose. The soy protein isolate has a dry basis protein content of not less than 90%; the pectin purity is not less than 90%, and the degree of esterification is 80%; the powdered soy lecithin has a purity of not less than 95% and is sieved through a 250μm sieve before addition; the food-grade glucose has a purity of not less than 99%. In this embodiment, based on 100 parts by weight of structured soy protein-pectin composite particles, the amount of powdered soy lecithin is 1.5 parts by weight, the sugar content of the solid sample is 5.0 wt%, and the target moisture content is 5.0 wt%.

[0080] In the preparation process, 1000g of soy protein isolate was weighed and mixed with 4556g of deionized water. The mixture was stirred at 350 rpm for 12 min under normal pressure and air atmosphere to obtain a protein dispersion system with a raw material solid content of 18 wt%. The pH of the system was adjusted to 11.2 using a 1.0 mol / L sodium hydroxide aqueous solution, and stirred at 35°C for 35 min. Under stirring at 350 rpm, food-grade anhydrous citric acid was added in batches to bring the pH back to 7.0, and stirring was continued for 5 min. The resulting spray-fed suspension was spray-dried at an inlet air temperature of 185°C, an outlet air temperature of 90°C, and an atomization pressure of 0.18 MPa, and the primary soy protein isolate powder was collected. In this embodiment, the particle size D50 of the primary soy protein isolate powder was 80 μm.

[0081] In the post-processing step, 1000g of primary soybean protein isolate powder from this embodiment was added to a fluidized bed. The bed temperature was stabilized at 60℃, and spray agglomeration was performed using 200g of deionized water as the agglomeration solution at a spray pressure of 0.20MPa for 25min. After spraying, drying continued for 20min to obtain three-dimensional porous agglomerated particles with a particle size D50 of 250μm. 63.8g of pectin was weighed and mixed with 1531.2g of deionized water, and stirred at 300r / min for 40min at 70℃ to obtain a pectin solution with a mass fraction of 4.0wt%. 1000g of three-dimensional porous agglomerated particles (dry basis) were added to a fluidized bed, and the pectin solution was sprayed at a bed temperature of 55℃ for 25min. After spraying, the particles were dried to a moisture content of 5.0wt% to obtain structured soybean protein-pectin composite particles. In this embodiment, the pectin interface layer had a mass fraction of 6.0wt% and a bulk density of 400kg / m³.

[0082] For compounding, packaging, and quality testing, 1000g of the structured soybean protein-pectin composite granules of this embodiment were taken, and 15.0g of sieved powdered soybean lecithin and 53.4g of food-grade glucose were added. The mixture was stirred at 35℃ and 30r / min for 20min. After nitrogen replacement, the mixture was sealed and packaged to obtain a low-sugar soybean protein compound solid beverage in solid form before reconstitution. Three parallel tests were performed on the solid sample of this embodiment. The average moisture content was 5.0wt%, with a standard deviation of 0.1wt%; the average sugar content was 5.0wt%, with a standard deviation of 0.1wt%; the average pectin interface layer mass fraction was 6.0wt%, with a standard deviation of 0.2wt%; the average three-dimensional porous aggregate particle size D50 was 250μm, with a standard deviation of 6μm; and the average bulk density was 400kg / m³, with a standard deviation of 9kg / m³.

[0083] Features of the solution in this embodiment

[0084] This embodiment adopts a high-load implementation scheme, with the proportion of pectin interface layer, the amount of powdered soybean lecithin, powder moisture and particle size all in the high value range, which is suitable for low-sugar instant solid beverages that require strong particle structure retention.

[0085] Example 3

[0086] In this embodiment, the key parameters are set as follows: the solid content of the spray-fed suspension is 14 wt%, the particle size D50 of the primary soy protein isolate powder is 50 μm, the particle size D50 of the three-dimensional porous aggregated particles is 180 μm, the mass fraction of the pectin interface layer is 3.5 wt%, the amount of powdered soy lecithin is 0.8 parts by mass, the sugar content of the solid sample is 2.5 wt%, and the moisture content is 3.5 wt%. The degree of pectin esterification is 65%, and the loose density of the structured soy protein-pectin composite particles is 300 kg / m³. The soy protein isolate, pectin, powdered soy lecithin, and glucose are all commercially available food-grade raw materials.

[0087] The specific preparation process is as follows: 1000g of soy protein isolate was weighed and mixed with 6143g of deionized water. The mixture was stirred at 320 rpm for 10 min under normal pressure and air atmosphere to obtain a protein dispersion system. The pH of the system was adjusted to 10.7 using a 1.0 mol / L sodium hydroxide aqueous solution, and stirred at 28℃ for 25 min. Under stirring at 320 rpm, the pH of the system was adjusted back to 6.7 in batches using food-grade anhydrous citric acid, and stirring was continued for 6 min. The pH-adjusted system was then spray-dried at an inlet air temperature of 172℃ and an outlet air temperature of 82℃ to obtain primary soy protein isolate powder.

[0088] 1000g of primary soy protein isolate powder from this embodiment was added to a fluidized bed, and the bed temperature was adjusted to 52°C. Spray agglomeration was performed using 140g of deionized water as the agglomeration solution at a spray pressure of 0.12MPa for 18 minutes. After spraying, drying continued for 15 minutes to obtain three-dimensional porous agglomerated particles. Separately, 36.3g of food-grade pectin with a degree of esterification of 65% was added to 1415g of deionized water and stirred at 60°C for 28 minutes to prepare a pectin solution with a mass fraction of 2.5wt%. The pectin solution was sprayed onto the surface of 1000g of three-dimensional porous agglomerated particles (dry basis) at a bed temperature of 48°C for 18 minutes. After spraying, drying was carried out until the moisture content was 3.5wt%, yielding structured soy protein-pectin composite particles.

[0089] Take 1000g of the structured soybean protein-pectin composite granules of this embodiment, and 8.0g of powdered soybean lecithin. The powdered soybean lecithin was sieved through a 200μm sieve before addition, and the undersize material was collected. Separately, take 25.9g of food-grade glucose. Add all three to a mixer and mix for 12 minutes at 28℃ and 22r / min. After mixing, the material is nitrogen-purged and sealed in packaging to obtain a low-sugar soybean protein compound solid beverage.

[0090] Quality testing methods and results

[0091] Three parallel tests were performed on the samples in this embodiment. Dry powder particle size analysis showed that the average D50 of the primary soy protein isolate powder was 50 μm with a standard deviation of 3 μm, and the average D50 of the three-dimensional porous aggregated particles was 180 μm with a standard deviation of 5 μm. The average mass fraction of the pectin interface layer was 3.5 wt% with a standard deviation of 0.1 wt%. The average moisture content was 3.5 wt% with a standard deviation of 0.1 wt%. The average sugar content was 2.5 wt% with a standard deviation of 0.1 wt%. The average bulk density was 300 kg / m³ with a standard deviation of 8 kg / m³.

[0092] Applicable Scenarios of This Embodiment

[0093] The proportions and process parameters in this embodiment are in the middle range, taking into account the stability of powder preparation, the ability to maintain particle structure, and the convenience of reconstitution. It is suitable for continuous preparation and sealed packaging of conventional low-sugar plant protein solid beverage production lines.

[0094] Example 4

[0095] I. Preparation Object and Raw Material State: A low-sugar soy protein compound solid beverage was prepared using commercially available food-grade soy protein isolate, food-grade pectin, food-grade powdered soy lecithin, food-grade glucose, and deionized water as raw materials. The soy protein isolate had a dry basis protein content of not less than 90%, a pectin purity of not less than 90%, and a pectin esterification degree of 78%. The powdered soy lecithin had a purity of not less than 95%, and the glucose had a purity of not less than 99%. The powdered soy lecithin was sieved through a 245μm sieve before addition, and the sieve-undersized material was collected.

[0096] II. Preparation of Primary Protein Powder: 1000g of soy protein isolate was weighed and mixed with 4882g of deionized water. The mixture was stirred at 330r / min for 10min under normal pressure and air atmosphere to obtain a protein dispersion system with a raw material solid content of 17wt%. The pH of the system was adjusted to 11.0 with 1.0mol / L sodium hydroxide aqueous solution and stirred at 22℃ for 33min. Subsequently, food-grade anhydrous citric acid was added in batches under stirring at 330r / min to adjust the pH of the system back to 6.9. The pH-adjusted system was spray-dried at an inlet air temperature of 180℃ and an outlet air temperature of 88℃ to obtain primary soy protein isolate powder with a particle size D50 of 75μm.

[0097] III. Particle Structure Construction: 1000g of primary soybean protein isolate powder from this embodiment was added to a fluidized bed and spray-agglomerated using 180g of deionized water as the agglomeration solution. The bed temperature was 58℃, the spray pressure was 0.18MPa, and the spray-agglomeration time was 20min. After spraying, drying continued for 12min to obtain three-dimensional porous aggregated particles with a particle size D50 of 245μm. 61.6g of pectin was weighed and mixed with 1559g of deionized water, and stirred at 300r / min for 20min at 68℃ to obtain a pectin solution with a mass fraction of 3.8wt%. The pectin solution was sprayed onto the surface of 1000g of three-dimensional porous aggregated particles (dry basis) at a bed temperature of 53℃ for 22min. After spraying, drying was carried out until the moisture content was 4.8wt%, resulting in structured soybean protein-pectin composite particles. In this embodiment, the pectin interface layer had a mass fraction of 5.8wt% and a bulk density of 390kg / m³.

[0098] IV. Compounding and Sealing Packaging: Take 1000g of the structured soybean protein-pectin composite granules of this embodiment, add 10.0g of sieved powdered soybean lecithin and 1.0g of food-grade glucose, and mix for 18min at 33℃ and 28r / min. After mixing, the material is nitrogen-purged and then sealed and packaged to obtain a low-sugar soybean protein compound solid beverage in solid form before reconstitution. The solid sample of this embodiment has a sugar content of 0.1wt% and a moisture content of 4.8wt%.

[0099] V. Quality Testing Methods and Results: Three parallel tests were conducted on the samples from this embodiment. Dry powder particle size analysis showed that the average D50 of the three-dimensional porous aggregated particles was 245 μm, with a standard deviation of 6 μm. The average mass fraction of the pectin interface layer was 5.8 wt%, with a standard deviation of 0.2 wt%. The average moisture content was 4.8 wt%, with a standard deviation of 0.1 wt%. The average sugar content was 0.1 wt%, with a standard deviation of 0.02 wt%. The average bulk density was 390 kg / m³, with a standard deviation of 8 kg / m³.

[0100] The process features and application directions of this embodiment

[0101] This embodiment uses particle size, bulk density, and pectin interface layer close to the high value range, while maintaining a low sugar content, making it suitable for instant solid beverages that require good packaging stability and low sugar formulation properties.

[0102] Comparative Example 1

[0103] The process is basically the same as in Example 1, except that in S1, the pH of the system is adjusted to 9.6 using a 1.0 mol / L sodium hydroxide aqueous solution, while other conditions remain unchanged.

[0104] Comparative Example 2

[0105] The method is basically the same as in Example 1, except that the total solids content of the protein dispersion system in S1 is adjusted to 8 wt%. Specifically, 1000g of soy protein isolate is weighed and mixed with 11500g of deionized water, while other conditions remain unchanged.

[0106] Comparative Example 3

[0107] The process is basically the same as in Example 1, except that in S1 the inlet air temperature of the spray drying is adjusted to 150°C, the outlet air temperature remains 75°C, the atomization pressure remains 0.12MPa, and other conditions remain unchanged.

[0108] Comparative Example 4

[0109] The process is basically the same as in Example 1, except that in S2, 50g of deionized water is used as the agglomeration liquid, which is equivalent to using 5 parts by mass of agglomeration liquid based on 1000g of primary soy protein isolate powder. Other conditions remain unchanged.

[0110] Comparative Example 5

[0111] The process is basically the same as in Example 1, except that in S2 the spray pressure is adjusted to 0.25 MPa, the bed temperature remains at 45°C, the spray agglomeration time remains at 12 min, and other conditions remain unchanged.

[0112] Comparative Example 6

[0113] The process is basically the same as in Example 1, except that the mass fraction of the pectin solution in S3 is adjusted to 0.5 wt%. Specifically, 7.7 g of pectin is weighed and added to 1522.3 g of deionized water, stirred at 250 r / min for 15 min at 50 °C, and then sprayed. Other conditions remain unchanged.

[0114] Comparative Example 7

[0115] The method is basically the same as in Example 1, except that the amount of powdered soybean lecithin in S4 is adjusted to 1.0g, which is equivalent to using 0.1 parts by weight of powdered soybean lecithin based on 1000g of structured soybean protein-pectin composite particles. Other conditions remain unchanged.

[0116] Comparative Example 8

[0117] The process is basically the same as in Example 1, except that the mixing time of the structured soybean protein-pectin composite particles and the sieved powdered soybean lecithin in S4 is adjusted to 2 minutes, while other conditions remain unchanged.

[0118] Comparative Example 9

[0119] The process is essentially the same as in Example 1, except that the pectin solution spraying step in S3 is omitted. The three-dimensional porous aggregated particles obtained in S2 are further dried under hot air at 45°C until the moisture content reaches 2.0 wt%, and then directly proceed to S4, with other conditions remaining unchanged. This comparative example is used to verify the synergistic effect between the core of the three-dimensional porous aggregated particles and the pectin interface layer.

[0120] Comparative Example 10

[0121] The experiment was essentially the same as in Example 1, except that the fluidized bed spray agglomeration step in S2 was omitted. Instead, the primary soybean protein isolate powder obtained in S1 was directly added to the fluidized bed as the core particles, and then sprayed with a 1.0 wt% pectin solution under the conditions of S3, followed by drying until the moisture content was 2.0 wt%, while other conditions remained unchanged. This comparative example was used to verify the synergistic effect between the core of the three-dimensional porous agglomerated particles and the pectin interface layer.

[0122] Comparative Example 11

[0123] The experiment was essentially the same as in Example 1, except that powdered soybean lecithin was not added in S4. Instead, 1000g of structured soybean protein-pectin composite particles were directly mixed at 20°C and 15r / min for 5 minutes, followed by nitrogen filling and sealing. Other conditions remained unchanged. This comparative example was used to verify the synergistic effect of structured soybean protein-pectin composite particles and powdered soybean lecithin.

[0124] Characterization and performance testing

[0125] The following characterization and performance tests are used for relative evaluation between the same set of examples and comparative examples. Unless otherwise specified, each sample was tested in triplicate, and the results are expressed as mean ± standard deviation. The same sample pretreatment method, the same instrument conditions, the same test parameters, and the same calculation caliber were used for the same index in the examples and comparative examples to ensure data comparability.

[0126] The dry powder particle size distribution test of structured soybean protein-pectin composite granules is used to evaluate whether the agglomeration scale supports reconstitution dispersion and particle integrity. Dried granules or final solid beverage powder are dispersed under low pressure using a dry powder injector and then measured using a laser diffractometer. The D50 value is recorded when the cumulative volume distribution reaches 50%, and D10, D90, and distribution span are recorded simultaneously. The test is performed in triplicate. The same dry powder injection method, dispersion pressure, and particle size distribution calculation aperture are used for testing in the same set of examples and comparative examples. The corresponding data fields are the average D50 and the standard deviation of D50, in μm. A D50 value within the target range with a smaller distribution span is considered superior.

[0127] The pectin interface layer mass fraction and solid moisture content were tested to evaluate the degree of interface layer formation and drying quality. Three-dimensional porous aggregated particles and structured soybean protein-pectin composite particles were collected before and after spraying, and their dry weights were recorded. The pectin interface layer mass fraction was calculated based on the difference in dry weight before and after spraying. Moisture content was measured using the loss on drying method, with the mixed solid sample as the object. Drying was performed under constant temperature conditions until the mass change stabilized, repeated three times. The corresponding fields are the mean and standard deviation of the pectin interface layer mass fraction and the mean and standard deviation of the moisture content, in wt%.

[0128] The bulk density test of structured soybean protein-pectin composite granules is used to evaluate the powder processing window and packaging stability. The dried granules are taken as samples. For samples with a pectin interface layer, the granules are structured soybean protein-pectin composite granules. For comparative samples without a pectin interface layer, the granules are three-dimensional porous aggregated granules before the compounding step. The granules are added naturally to a graduated cylinder or density cup of known volume without being compacted. After leveling, the mass of the sample entering the container is weighed, and the bulk density is calculated by dividing the mass by the container volume. Each sample is packed three times in parallel, avoiding knocking and compaction. The corresponding data fields are the average bulk density and the standard deviation of bulk density, in kg / m³. Values ​​within the set range and with small batch-to-batch fluctuations are preferred.

[0129] The reconstitution and dispersion time test of low-sugar soy protein compound solid beverages was used to evaluate the rapid wetting and dispersion ability of powders in low-sugar systems. Solid samples were added to deionized water at 25℃ at a concentration of 80 g / L. The same impeller type, stirring speed, container diameter, liquid level, and stirring position were used for stirring. The time from the time the sample was added until no longer visible floating dry powder clumps and unwetted agglomerates were observed on the liquid surface was recorded. Each sample was tested in triplicate, and the results are expressed as mean ± standard deviation. The corresponding data fields are the mean and standard deviation of the reconstitution and dispersion time, in seconds (s). Lower values ​​indicate faster reconstitution and dispersion.

[0130] The centrifugal sedimentation rate test was used to evaluate the liquid-phase stability of low-sugar soy protein compound solid beverages after reconstitution. The sample was prepared by mixing it with water at 25°C at a concentration of 80 g / L solid sample and stirring for 2 min. After standing for 10 min, an equal volume of the reconstituted solution was taken and treated under the same centrifugal force, centrifugation time, and centrifugation temperature. The supernatant was discarded, and the wet mass of the precipitate was weighed. The centrifugal sedimentation rate was calculated as a percentage of the wet mass of the precipitate to the original mass of the reconstituted solution. The test was performed in triplicate, with consistent centrifugal force, centrifugation time, centrifugation temperature, centrifuge tube specifications, and sample volume for the same set of examples and comparative examples. The corresponding fields are the average and standard deviation of the centrifugal sedimentation rate, in wt%. Lower values ​​indicate better stability of the reconstituted solution.

[0131] The precipitation index test was used to evaluate the precipitation changes of low-sugar soy protein compound solid beverages during the settling process. Samples were prepared by mixing 80 g / L of solid sample with water at 25°C and stirring for 2 minutes. The mixture was then placed in a container of the same size and allowed to stand at 25°C. The wet mass of the precipitate was recorded at the same preset settling time point (60 minutes as the end point) for each sample. The precipitation index was calculated as the percentage of the wet mass of the precipitate to the original mass of the prepared beverage. The sampling amount, settling container, settling temperature, settling time point, and weighing method were kept consistent for the same set of examples and comparative examples.

[0132] The fine powder percentage test after particle oscillation is used to evaluate the structural integrity of the combination of three-dimensional porous aggregated particles and pectin interface layer. A sealed solid sample is placed in a fixed-volume container and mechanically oscillated for 10 minutes at the same oscillation frequency and amplitude. Subsequently, it is lightly sieved through an 80-mesh sieve, and the mass of the fine powder passing through the sieve is weighed. The fine powder percentage is calculated as a percentage of the mass of the fine powder passing through the sieve relative to the mass of the sample before oscillation. Each sample is tested in triplicate. The sample amount, container specifications, oscillation frequency, amplitude, oscillation time, and sieving method are kept consistent within the same set of examples and comparative examples. The corresponding fields are the average and standard deviation of the fine powder percentage after oscillation, in wt%. Lower values ​​indicate better particle structure retention.

[0133] Sugar content testing of solid samples in low-sugar soy protein compound solid beverages was used to evaluate their low-sugar properties. Sugar content was based on the total mass of the solid sample before reconstitution, and was calculated as the total amount of free monosaccharides and disaccharides in the solid sample. The sugar content was quantified and summed after water extraction, separation of insoluble matter, and subsequent addition. The corresponding fields are the average sugar content and standard deviation, in wt%.

[0134] All data are mean ± standard deviation. The concentration of solid samples used in the reconstitution performance test was 80 g / L. D50 is the D50 of the final solid beverage powder of each sample; the pectin interface layer mass fraction is based on the dry mass of the structured soybean protein-pectin composite particles; moisture and sugar content are measured based on the final solid beverage; bulk density is the bulk density of the protein particle component before entering the final compounding step, wherein the protein particle component of Comparative Example 9 is a three-dimensional porous aggregated particle without pectin coating.

[0135] Table 1 Performance of Examples and Comparative Examples

[0136] Figures 1 to 4 This is a single-factor experimental result diagram based on the intermediate parameter scheme shown in Example 3, used to illustrate the synergistic effects of the pectin interface layer, powdered soybean lecithin, three-dimensional porous agglomerate particle size, and spray agglomeration water volume on dispersibility and sedimentation stability. Figure 1 To illustrate the effect of varying the pectin interfacial layer mass fraction based on the intermediate parameter scheme shown in Example 3, a single-factor plot was created using 0.8 parts by weight of powdered soybean lecithin, a three-dimensional porous aggregated particle D50 of approximately 180 μm, and 14 parts by weight of deionized water for spray agglomeration. The results showed that when the pectin interfacial layer mass fraction was between approximately 2.0 and 5.2 wt%, both the reconstitution dispersion time and centrifugal sedimentation rate remained at low levels. Insufficient interfacial layer resulted in inadequate interfacial regulation and stabilization, while excessively high interfacial layer content increased particle surface adhesion and hydration resistance. Therefore, a suitable pectin interfacial layer can form an effective hydrophilic coating on the particle surface, which is beneficial for improving the wetting penetration and suspension stability of low-sugar soybean protein compound solid beverages during reconstitution.

[0137] Figure 2 This is a single-factor effect diagram of varying the amount of powdered soybean lecithin based on the intermediate parameter scheme shown in Example 3. Under the conditions of a pectin interfacial layer mass fraction of 3.5 wt%, a three-dimensional porous aggregated particle D50 of approximately 180 μm, and 14 parts by mass of deionized water for spray agglomeration, only the amount of powdered soybean lecithin was varied. The results show that when the amount of powdered soybean lecithin is approximately 0.4-1.2 parts by mass, the reconstitution dispersion time and centrifugal sedimentation rate are lower, indicating that lecithin can reduce the interfacial resistance between the powder and the aqueous phase and promote rapid wetting and dispersion of particles. However, when the amount is too low, the interfacial regulation effect is insufficient, while when the amount is too high, it may lead to local hydrophobic aggregation or enhanced surface adhesion. Therefore, it is evident that simply increasing the amount of lecithin cannot continuously improve performance; rather, it needs to be appropriately matched with the pectin interfacial layer and the aggregated structure.

[0138] Figure 3To investigate the single-factor influence of changing the D50 of the three-dimensional porous agglomerated particles based on the intermediate parameter scheme shown in Example 3, under the conditions of a pectin interface layer mass fraction of 3.5 wt%, a powdered soybean lecithin content of 0.8 parts by mass, and 14 parts by mass of deionized water for spray agglomeration, only the D50 of the agglomerated particles was changed. The results showed that when the D50 was approximately 145-230 μm, the mixing and dispersion time and centrifugal sedimentation rate were in the optimal range; when the particle size was too small, the powder was prone to fine powdering, dispersion, and agglomeration, while when the particle size was too large, it may reduce the overall deagglomeration efficiency after water enters the particle interior. Figure 4 To illustrate the effect of varying the amount of deionized water used in spray agglomeration based on the intermediate parameter scheme shown in Example 3, a single-factor plot was created by changing the amount of deionized water used in spray agglomeration, under the conditions of a pectin interface layer mass fraction of 3.5 wt%, a powdered soybean lecithin content of 0.8 parts by mass, and a three-dimensional porous agglomerate particle D50 of approximately 180 μm. The results showed that when the amount of deionized water was approximately 10-18 parts by mass, the dispersion time and sedimentation rate were lower, indicating that an appropriate amount of water helps to form stable solid bridges and a porous agglomerate framework between the primary powders; insufficient water leads to insufficient agglomeration, while excessive water can easily cause excessive adhesion of the structure or reduction of pores. The above results collectively demonstrate that this scheme, through the matching of the interface layer, surface-active components, agglomerate particle size, and spray water volume, can improve the mutually restrictive problems of rapid reconstitution, anti-settling, and powder structure stability in low-sugar systems.

[0139] Figures 5 to 7 The structural basis formed by the above parameter optimization is further verified from the perspectives of particle size distribution and particle morphology. Figure 5 The following are the particle size difference distribution diagrams of dry powder in Examples 1, 4, and 10. The particle size distribution of Example 1 is mainly concentrated in the medium particle size range, with a relatively concentrated peak shape and a low proportion of fine powder. This indicates that the present solution can effectively construct the primary powder into three-dimensional porous aggregated particles with more uniform particle size, thereby reducing the problems of powder flying, clumping, and uneven wetting caused by fine powdering. Figure 6 The cumulative particle size distribution diagrams for Example 1, Comparative Example 4, and Comparative Example 10 show that the D50 corresponding to the cumulative distribution curve of Example 1 is within a moderate particle size range, Comparative Example 10 is clearly biased towards the small particle size range, and Comparative Example 4 exhibits a wide distribution characteristic. This indicates that after canceling or weakening controlled agglomeration, it is difficult for the powder to obtain a stable and concentrated hundred-micron-level particle size structure. The particle size distribution results show that the particle size formed in Example 1 avoids both the problems of poor wetting and easy sedimentation of primary fine powder and the problem of slow dispersion of excessively large agglomerates.

[0140] Figure 7The images show statistical representations of particle morphology for Examples 1, 4, and 10. Particle structure characteristics are characterized by pore area ratio and roundness index. The pore area ratio, calculated using particle images acquired at the same magnification, is the percentage of the pore area within the particle's projected area to the total projected area after binarization. The roundness index is calculated as 4π × particle projected area / particle projected perimeter². The results show that Example 1 exhibits both a high pore area ratio and high roundness, indicating that the particles not only form a relatively complete aggregate shape but also retain pore structures within and between particles that facilitate water penetration. Compared to the comparative examples, this structure allows the aqueous phase to quickly penetrate the particles, promoting wetting and deagglomeration from the outside in. This structural explanation reveals the advantages of Example 1 in terms of dispersion time and sedimentation stability.

[0141] Figures 8 to 10 The actual effectiveness of this solution is explained through three consecutive stages: interface layer formation, wetting and mixing process, and static stability. Figure 8 The image shows the scatter plot of the pectin interface layer mass fraction for Examples 1, 6, and 9. The pectin interface layer mass fraction in Example 1 was approximately 1.5 wt%, higher than that in Comparative Example 6 and significantly higher than that in Comparative Example 9, which did not form an effective interface layer. This result indicates that pectin spraying treatment can increase the amount of pectin adhering to the surface of agglomerated particles, consistent with the formation of a hydrophilic interface structure. This is beneficial for regulating the interfacial state of soybean protein powder in the aqueous phase and reducing the possibility of flocculation or sedimentation after direct contact of protein particles.

[0142] Figure 9 The diagrams show the rehydration, wetting, and dispersion processes of Examples 1, 7, and 11. The proportion of unwetted agglomerates gradually decreases with rehydration time, with Example 1 showing the fastest decrease and approaching zero earlier. This result indicates that, through the combined effects of the three-dimensional porous agglomerates providing moisture channels, the pectin interface layer providing hydrophilic protection, and lecithin regulating interface wetting, Example 1 can reduce powder floating, dry core, and clumping. Figure 10 The diagram shows the sedimentation stabilization process of the prepared solutions in Examples 1, 9, and 11. In Example 1, the sedimentation index remained low within 60 minutes of standing, while the sedimentation indices of Comparative Examples 9 and 11 increased more significantly. This indicates that the proposed method not only improves the wetting and dispersion speed in the initial stage of preparation but also maintains good suspension stability after preparation, avoiding common problems in low-sugar soy protein drinks such as rapid sedimentation, flavor stratification, and system inhomogeneity.

[0143] Figure 11 and Figure 12 This is used to illustrate the mechanical stability of the solution during powder storage, transportation, and use. Figure 11The graph shows the relationship between the loose packing density and the fine powder ratio after vibration for Example 1, Comparative Example 4, and Comparative Example 8. Example 1 still has a low fine powder ratio after vibration when the loose packing density is 200 kg / m³, while the fine powder ratio of Comparative Example 4 is significantly increased. This indicates that the agglomerated particles formed by this scheme are not loose and fragile structures, but achieve a good balance between porosity and particle strength. Figure 12 The image shows the scatter plot of the fine powder percentage after vibration for Examples 1, 4, and 8. The fine powder percentage after vibration for Example 1 is approximately 8.5 wt%, lower than that for Comparative Example 4, and close to that of Comparative Example 8. This result further illustrates that the particles obtained in Example 1 are less likely to break into fine powder under vibration conditions, which can reduce problems such as increased powder flying during storage and transportation, decreased reconstitution performance, and poor powder uniformity.

[0144] Figure 13 and Figure 14 Further comparison of macroscopic photographs and SEM microstructures visually verifies the role of the fluidized bed spray agglomeration step and the three-dimensional porous agglomeration core in the formation of the final powder structure. Figure 13 This is a comparison image of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 10, wherein... Figure 13 a is a macroscopic optical photograph of the final product of Example 1. The sample is a low-sugar soybean protein compound solid beverage, which is mainly composed of three-dimensional porous aggregated particles with a particle size of about 120 μm (D50), containing about 1.5 wt% pectin interface layer and about 0.2 wt% powdered soybean lecithin. The whole is in a light milky white to milky white loose powder state, indicating that this scheme can still form a relatively light and uniform aggregated powder structure under low sugar and low addition conditions. Figure 13 b is a macroscopic optical photograph of the final product of Comparative Example 10. Comparative Example 10 eliminated the S2 fluidized bed spray agglomeration step, directly using primary soy protein isolate powder with a particle size D50 of approximately 20 μm as the core particles for pectin spraying and lecithin compounding. The final solid beverage powder had a D50 of 42 μm, exhibiting more pronounced fine powder characteristics. This comparison demonstrates that simply compounding interfacial components is insufficient to obtain ideal reconstituted powders; controlled formation of three-dimensional porous agglomerates at the hundred-micron level is a crucial prerequisite for improving the macroscopic powder morphology.

[0145] Figure 14 The image shows a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 10, which is used to further illustrate the key role of the core of the three-dimensional porous agglomerated particles in the integrity of the final powder microstructure. Figure 14 a is a low-magnification SEM image of the final product of Example 1, showing multiple three-dimensional porous aggregated particles with a D50 of approximately 120 μm distributed in the field of view, indicating that Example 1 can form a stable aggregated structure at the hundred-micron level. Figure 14b is a low-magnification SEM image of the final product of Comparative Example 10, showing that it is mainly composed of fine particles of primary soy protein isolate powder with a D50 of about 20 μm, indicating that the particle size was significantly reduced after the S2 step was removed. Figure 14 c is a medium-magnification SEM image of the final product of Example 1. It can be seen that a single or a few three-dimensional porous agglomerates have a rough outline, primary particle bridging and inter-particle channels, indicating that the 20μm primary powder forms a hierarchical agglomerate after being agglomerated by fluidized bed spray. Figure 14 Image d is a medium-magnification SEM image of the final product of Comparative Example 10, showing only fine primary particles and their local secondary adhesions, without forming a continuous porous aggregate framework. Figure 14 e is a high-magnification SEM image of the final product of Example 1, which shows the solid bridging between particles, the rough surface structure, and the local continuity features after the formation of the pectin interface layer. Combined with the calculation results of the dry weight difference before and after spraying, this morphology is consistent with the processing results of pectin adhering to the surface of the three-dimensional porous aggregate core. Figure 14 f is a high-magnification SEM image of the final product of Comparative Example 10, showing that there is only local deposition on the surface of the primary particles and insufficient pore structure, indicating that the lack of an aggregate core of about 120 μm will weaken the interparticle connection and the ability to maintain the porous structure.

[0146] In conclusion, Figures 1 to 14 A progressive verification relationship was established from aspects such as parameter optimization, particle size distribution, morphology and structure, interface layer formation, reconstitution process, sedimentation stability, anti-breakage property, and macro-microstructure comparison. The results show that by constructing three-dimensional porous aggregated particles with moderate particle size and matching a pectin interface layer and a small amount of powdered soybean lecithin on their surface, this method can simultaneously improve the problems of easy dispersion of fine powder, slow wetting, easy agglomeration, rapid sedimentation, and increased fine powder rate after storage and transportation in low-sugar soybean protein compound solid beverages. The resulting powder has good reconstitution and dispersibility, suspension stability, and structural stability.

[0147] As can be seen from the performance trends of the examples and comparative examples in Table 1, Examples 1-4 maintained consistency with the technical solution in terms of D50, pectin interface layer mass fraction, moisture, bulk density, and sugar content, while achieving a good overall balance in terms of reconstitution dispersion time, centrifugal sedimentation rate, and fine powder rate after shaking. Example 3, located in the intermediate ratio and intermediate process zone, showed low reconstitution dispersion time, sedimentation rate, and fine powder rate, indicating that the combination of hierarchical particle structure, appropriate amount of pectin interface layer, and powdered soybean lecithin has good overall compatibility. After changing pH, solids content, spray drying, agglomeration liquid, spray pressure, pectin solution concentration, powdered soybean lecithin dosage, and mixing time in Comparative Examples 1-8, the relevant indicators deviated in different directions. Comparative Examples 9-11 further showed that when any synergistic element of three-dimensional porous agglomerates, pectin interface layer, and powdered soybean lecithin is missing, the structural retention or reconstitution stability will deteriorate to varying degrees.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A low-sugar soy protein compound solid beverage, characterized in that, Based on the solid form before reconstitution, the low-sugar soybean protein compound solid beverage includes structured soybean protein-pectin composite particles and powdered soybean lecithin. The structured soybean protein-pectin composite particles include a core formed of soybean protein isolate and a pectin interface layer formed of pectin disposed on the surface of the core. The core is a three-dimensional porous aggregated particle with a particle size D50 of 120-250 μm. The pectin interface layer accounts for 1.5-6.0 wt% of the dry weight of the structured soybean protein-pectin composite particles. Based on 100 parts by weight of the structured soybean protein-pectin composite particles, the amount of powdered soybean lecithin is 0.2-1.5 parts by weight. Based on the total weight of the low-sugar soybean protein compound solid beverage in solid form before reconstitution, the sugar content of the low-sugar soybean protein compound solid beverage, calculated as the total amount of free monosaccharides and disaccharides, is 0-5.0 wt%, and the moisture content is 2.0-5.0 wt%.

2. The low-sugar soybean protein compound solid beverage according to claim 1, characterized in that, The particle size D50 of the three-dimensional porous aggregated particles is 145-230 μm.

3. The low-sugar soybean protein compound solid beverage according to claim 1, characterized in that, The pectin interface layer accounts for 2.0-5.2 wt% of the dry weight of the structured soybean protein-pectin composite particles.

4. The low-sugar soybean protein compound solid beverage according to claim 1, characterized in that, Soy protein isolate primary powder is prepared through the following steps and used as a raw material for preparing the three-dimensional porous aggregated particles: A1. Mix soy protein isolate with deionized water; A2. Adjust the pH of the system to 10.2-11.2 with sodium hydroxide and stir at 20-35℃ for 15-35 min; A3. Adjust the pH of the system to 6.4-7.0 using anhydrous citric acid under stirring conditions; A4. Spray dry the system after pH adjustment, with an inlet air temperature of 160-185℃ and an outlet air temperature of 75-90℃, to obtain the primary soy protein isolate powder, wherein the particle size D50 of the primary soy protein isolate powder is 20-80μm.

5. The low-sugar soybean protein compound solid beverage according to claim 4, characterized in that, The three-dimensional porous agglomerated particles are prepared by the following steps: B1. Add the primary soy protein isolate powder to a fluidized bed; B2. Based on 100 parts by weight of the soy protein isolate primary powder, 8-20 parts by weight of deionized water are used as the agglomeration liquid for spray agglomeration. The spray agglomeration is carried out under the conditions of bed temperature of 45-60℃, spray pressure of 0.05-0.20MPa, and spray agglomeration time of 12-25min. B3. Continue drying the spray-agglomerated material for 10-20 minutes to obtain the three-dimensional porous agglomerated particles.

6. The low-sugar soybean protein compound solid beverage according to claim 5, characterized in that, The pectin interface layer is constructed through the following steps: C1. Mix pectin with deionized water; C2. Stir the mixture of pectin and deionized water at 50-70℃ for 15-40 min to obtain a pectin solution with a mass fraction of 1.0-4.0 wt%. C3. Spray the pectin solution onto the surface of the three-dimensional porous aggregated particles. The bed temperature during spraying is 40-55℃, and the spraying time is 10-25 minutes. C4. Dry the sprayed particles until the moisture content is 2.0-5.0 wt% based on the mass of the structured soybean protein-pectin composite particles, to obtain the structured soybean protein-pectin composite particles.

7. The low-sugar soybean protein compound solid beverage according to claim 6, characterized in that, The low-sugar soy protein compound solid beverage is prepared through the following steps: D1. Take the structured soybean protein-pectin composite particles and the powdered soybean lecithin, and add food-grade glucose when the target sugar content of the low-sugar soybean protein compound solid beverage is greater than 0 wt% and not higher than 5.0 wt%. Add all raw materials to the mixing equipment. D2. Mix at 20-35℃ and 15-30r / min for 5-20min; D3. After nitrogen replacement, the mixed materials are sealed and packaged to obtain the low-sugar soybean protein compound solid beverage.

8. The low-sugar soybean protein compound solid beverage according to claim 1, characterized in that, The low-sugar soybean protein compound solid beverage has the following technical features: The loose density of the structured soybean protein-pectin composite granules is 200-400 kg / m³. The degree of esterification of the pectin is 50-80%.

9. A method for preparing a low-sugar soybean protein compound solid beverage as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Preparation of structured soybean protein-pectin composite particles: Soybean protein isolate is mixed with deionized water, and the pH of the system is adjusted to 10.2-11.2 with sodium hydroxide and stirred at 20-35℃ for 15-35 min; under stirring conditions, the pH of the system is adjusted back to 6.4-7.0 with anhydrous citric acid; the pH-adjusted system is spray-dried at an inlet air temperature of 160-185℃ and an outlet air temperature of 75-90℃ to obtain primary soybean protein isolate powder; the primary soybean protein isolate powder is added to a fluidized bed, and 8-20 parts by weight of deionized water are used as the agglomeration liquid, based on 100 parts by weight of the primary soybean protein isolate powder. Spray agglomeration was carried out for 12-25 minutes at a bed temperature of 45-60℃ and a spray pressure of 0.05-0.20MPa, followed by drying for 10-20 minutes to obtain three-dimensional porous agglomerated particles. Pectin was mixed with deionized water and stirred at 50-70℃ for 15-40 minutes to obtain a pectin solution with a mass fraction of 1.0-4.0wt%. The pectin solution was sprayed onto the surface of the three-dimensional porous agglomerated particles at a bed temperature of 40-55℃ for 10-25 minutes. The sprayed particles were then dried to a moisture content of 2.0-5.0wt% to obtain the structured soybean protein-pectin composite particles. S2. When the target sugar content of the low-sugar soybean protein compound solid beverage is 0 wt%, raw materials for which free monosaccharides and disaccharides are not detected by the sugar content detection method are selected, and food-grade glucose is not added. The structured soybean protein-pectin composite particles are mixed with the powdered soybean lecithin to obtain a mixture. When the target sugar content of the low-sugar soybean protein compound solid beverage is greater than 0 wt% and not higher than 5.0 wt%, food-grade glucose calculated based on the total mass of the final product, the content of free monosaccharides and disaccharides in each raw material, and the target sugar content is mixed with the structured soybean protein-pectin composite particles and the powdered soybean lecithin to obtain a mixture. S3. Package the mixture to obtain the low-sugar soy protein compound solid beverage.

10. The preparation method according to claim 9, characterized in that, In step S1, the system after pH adjustment is used as a spray feed suspension. The raw material solids content of the spray feed suspension is 10-18 wt%. The raw material solids content is calculated based on the feed mass of soy protein isolate and deionized water, excluding the mass introduced by the pH adjuster. In step S2, the powdered soybean lecithin is sieved through a sieve with a pore size of 150-250μm before being added, and the sieve-less material is collected. In step S3, the mixture is sealed and packaged after being purged with nitrogen.

Citation Information

Patent Citations

  • A process for producing fast-dissolving soy protein isolate

    CN110250316B